Uji Network Pharmacology Dan Docking Moleculer Senyawa Metabolit Sekunder Begonia willemii Endemik Sulawesi Tengah Terhadap Reseptor Kanker Serviks - Jamal, Jamaluddin; Musnina , Wa Ode Sitti Musnina; Setiawan , Muh. Risky Setiawan; Rumi , Amelia (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
One of the most common types of cancer in Indonesia is cervical cancer. Cervical cancer is caused by infection with the Human Papilloma Virus (HPV) that grows in the cervix. Begonia willemii is a new plant in Central Sulawesi that is used as an anticancer. This study aims to determine the chemical compounds contained in the ethanol extract of Begonia willemii using LC-MS, and identify proteins that interact with the chemical compounds of Begonia willemii in the cervical cancer disease pathway, and determine the interaction between compounds contained in the ethanol extract of Begonia willemii with target proteins as cervical anticancer using the molecular docking method. This research method starts from sample preparation, then maceration extraction for three days using 96% ethanol solvent, the extract results are then analyzed using LC-MS, after which Network pharmacology is carried out to determine the target protein for cervical cancer and in molecular docking simulations with Autodock 4.2 software. The protein model was downloaded from the Protein Data Bank with the code 6GU2. The results of this study obtained a percentage yield of Begonia willemii extract of 10.52%, there was 1 compound component contained in the LC-MS results, namely 3-Chloro-4-methylaniline, and the results of Network pharmacology obtained CDK1 protein which has the highest degree value. Based on the results of molecular docking of the CDK1 protein (PDB ID: 6GU2), the affinity energy of the 3-Chloro-4-methylaniline compound was obtained at -5.4 kcal/mol and the affinity energy of Ribociclib (positive control) was -8.6 kcal/mol. The affinity energy of the natural ligand (Flavopiridol) was -9.9 kcal/mol. Based on these results, it is known that the 3-Chloro-4-methylaniline compound has an effectiveness that is not as strong as the natural ligands (Flavopiridol) and Ribociclib (positive control).